Study on the Impact of Step Layout on Secondary Energy Dissipation and Flow Pattern of Spillway Tailwater - YANG Ruiguo; QIU Yong; CHEN Yubin; YUE Cuiyun; YIN Xingtang (Renmin Zhujiang)
A secondary energy dissipation is required between the sill underflow stilling basin and the downstream tailrace at the outlet of the Dabaitian Reservoir spillway in Fengqing County,Yunnan Province.At the same time,the stepped energy dissipation section is connected through a 40° bend to adapt to the change of terrain.Through the hydraulic model test research,based on the original plan,after the water flowing out of the stilling basin passes through the stepped bend,an obvious Z-shaped folded water flow is produced on the plane.When it occurs once in 30 years,the water velocity on the left side of the bend reaches 9.97 m/s,threatening the stability of the rock formations along the slope of the left bank.The modified plan of step backward movement can effectively improve the flow pattern in the bend.On this basis,an improved plan to reduce the size of the original step (2.50 m×1.50 m to 1.00 m×0.60 m) is proposed to avoid falling water flow at the location of the step in the case of frequent small-flow floods.The research results show that in the improved stepped energy dissipation combination for bend,the water depth distribution along the cross section of the tailrace downstream of the stilling basin is relatively even in the case of small-flow floods,and the flow patten is improved significantly,so the water flowing back to the river smoothly is realized under frequent flood discharges.